Fish health problems in Laguna de Bay and environs. - Philippine Council for Agriculture; Forestry and Natural Resources Research and Development (Los Banos,Laguna PCARRD, 1988)
Book Series No. 49
Keywords: Laguna de Bay; Fish health; Fish